A dental clinic simulation for the study of patients and instruments circulation - Suwanna Eua-Atthakaroon (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The primary purposes of this study were to develop a model of dental services in the dental clinic at Prakonchai Hospital which concerned the flow of patients and dental instruments, and to analyze the performance of their services. Performance measures in the simulation model were waiting time and time of dental patient in system, and utilization time of dental units. In creating model, empirical and historical data were used, which came from the observation and records review in the real system. The methods selected for this study were queuing and simulation. The model was constructed using the general language C++. The events simulated were the arrival of dental patients, calling of patients, beginning services, departure of patients, and sterilizing of instruments. Model testing and validation were performed during and after model formulation for credibility and validity. The results indicated that the system could sufficiently provide dental services for the present. To retain this ability, maintaining dental instruments and dental units available at all times as well as having appropriate management in servicing were suggested. The developed model could be accepted as a baseline model. Collecting more data from other hospitals was recommended for developing the general model of dental service in the further studies.